EFEKTIVITAS PENERAPAN PLATFORM GOOGLE CLASSROOM DALAM PEMBELAJARAN PENJASKES SISWA SMAN 2 BUNGARAYA PADA MASA PANDEMI - Fendi Afrianto; Zainur Zainur; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Current learning activities cannot be carried out face-to-face. This is due to the Covid-19 pandemic. This study aims to determine the effectiveness of the implementation of the Google Classroom platform in learning physical education for students at SMA N 2 Bungaraya during the pandemic. This research was conducted at SMAN 2 Bunga Raya, Siak which is located at Jl. Hang Jebat Kp. Kemuning Muda, Bunga Raya District, Riau Province. The sampling technique in this study is a simple random sampling technique. The number of samples in this study were 88 respondents taken from class X and XI at SMA Negeri 2 Bungaraya. Research instruments that use a Likert scale can be made in the form of a checklist or multiple choice. The validity of the instrument used in this study is the validity of the construction. Based on the results of the study, it was shown that the effectiveness of the implementation of the google classroom platform in physical education learning for the students of SMAN 2 Bungaraya was classified as "Very Good". Based on the paired sample t test, it shows that learning using the google classroom platform is more effective compared to using manual time, and also the features on the google classroom platform can work well in the physical education learning process at SMAN 2 Bungaraya.Keywords: Effectiveness, google classroom, SMAN 2 Bunga Raya, physical education.